A practical theological approach to the challenge of poverty in post-1994 South Africa: Apostolic Faith Mission as a case study - Kgatle, Mookgo S. (HTS teologiese studies, 2017)
This article demonstrates a practical theological approach to the challenge of poverty in post-1994 South Africa by using Apostolic Faith Mission (AFM) as a case study. It argues that while the Reconstruction Development Plan, the Growth Employment and Reconstruction strategy, Accelerated Shared Growth Initiative for South Africa, New Growth Path and the National Development Plan have achieved some level of economic growth, the majority of people in South Africa still live in poverty. To establish this argument, the article starts first by describing the challenge of poverty in post-1994 South Africa. The different economic approaches to the challenge of poverty in post-1994 South Africa are also explained in detail. Lastly, the article elaborates on the ways in which the AFM through its local assemblies can alleviate poverty. The article concludes that the AFM is a collaborator to the post-1994 South African government.